Impacto de la ley de simplicidad y progresividad tributaria dentro de la economía del Ecuador 2020-2021. - Sarango Quiñonez, Naomi Mishel; Pacheco Vasquez, Nallely Patricia (Universidad Técnica de Machala, 2022)
The objective of this work was to determine the importance of the Law of Simplicity and Progressivity of Taxation in 2020 and 2021, focusing on the progressive changes that have been generated within the Ecuadorian economy, in which we have focused on central issues such as the creation of the Microenterprise Tax Regime and Changes in deductions in personal expenses. The research seeks to clear unknowns about the Law of Simplicity and Progressivity of Taxation. The methodology was based on a bibliographic review of scientific articles, where a compilation of documents was made, specifically of scientific articles housed in indexed journals to obtain the information that was later analyzed. In other theoretical foundations that also help to support the research variables. From the economic perspective, we analyze 2 types of variations in which the state benefits from this Law since it generates more income by breaching the principle of tax progressivity, meanwhile it affected the economy of microenterprises. CHAPTER I: The referential framework is found, where the problematization, justification, objectives and hypothesis are mentioned. CHAPTER II: The theoretical framework is found, which refers to several definitions with their corresponding authors, in order to understand the context of the research. CHAPTER III: The research methodology is established, with which the objectives are sought to be achieved. CHAPTER IV: The results obtained are mentioned, where the conclusions and recommendations for the development of the research are found.
El objetivo del presente trabajo fue determinar la importancia de la Ley de Simplicidad y Progresividad Tributaria en año 2020 y 2021, enfocándose en los cambios progresivos que se han ido generando dentro de la economía Ecuatoriana, en lo cual nos hemos enfocado en temas centrales como la creación del Régimen Impositivo de Microempresa y Cambios de deducciones en los gastos personales .La investigación busca despejar incógnitas sobre la Ley de Simplicidad y Progresividad Tributaria. La metodología se basó en una revisión bibliográfica de artículos científicos, donde se hizo una recopilación de documentos, específicamente de artículos científicos alojados en revistas indexadas para la obtención de la información que posteriormente fue analizada. En otros fundamentos teóricos que también ayudan a sustentar las variables de la investigación. Desde la perspectiva económica, analizamos 2 tipos de variaciones en la cual el estado se beneficia con esta Ley ya que genera más ingresos incumpliendo el principio de progresividad tributaria, mientras tanto afectó a la economía de las microempresas. CAPÍTULO I: Se encuentra el marco referencial, en donde se mencionan la problematización, la justificación, los objetivos e hipótesis. CAPÍTULO II: Se encuentra el marco teórico, mismo que hace alusión a varias definiciones con sus correspondientes autores, para comprender el contexto de la investigación. CAPÍTULO III: Se establece la metodología de la investigación, con la que se busca alcanzar los objetivos. CAPÍTULO IV: Se mencionan los resultados obtenidos, donde se encuentran las conclusiones y recomendaciones al desarrollo de la investigación.
Keywords: PROGRESIVIDAD; SIMPLICIDAD; ECONOMIA; INGRESOS